Integrated learning of integrated marking communication in Ubon Ratchathani University Thailand - HENRY FONJI ACHALEKE (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This study aims to assess students’ views on Integrated Learning as it pertains to the instruction and assessment of Integrated Marketing Communication (IMC). In particular, it assesses how students feel about non-traditional instructional methods, such as case studies, presentations, and a final term project.Method: In the first semester of 2007, twenty questionnaires were given out to third-year International Business students at Ubon Ratchathani University’s Faculty of Management Science. Content analysis was used to categorise participant responses, and statistical software was used to analyse the data.Findings: The results showed that students thought integrated learning was a great approach to education in the IMC programme. In addition, the term project gave students a rare chance to combine theory and practice, which improved their grasp and application of IMC.Implications/Novel contribution: This research is crucial. Students are more actively involved, learn more about the material, and have a firmer grasp on how to apply what they’ve learned in theory to real-world problems; these benefits form the basis for the value of integrated learning in IMC instruction.